Pembelajaran Tari Sigeh Penguten Menggunakan Strategi Joyful Learning Berbantu Dengan Humor Pada Kelas VIII di SMP Xaverius Pringsewu - Agata Shintia; Susi Wendhaningsih; Agung Kurniawan; I Wayan Mustika (Jurnal Seni dan Pembelajaran, 2018)
The foccuss in tresearch is how the proccess and the result after the Sigegh Penguten teahcing learning through joyful learning included humorous material for eighth grade students at Xaverius Pringsewu Junior High School. Behaviouristic theory was implemented in this research. Furthermore, qualitative descriptive was implemented as a design in tihs research. The population of this research was eighth grade of junior high school students, where as five of them were chosen as the sample, and art teacher. The instruments were observation, interview, documentation, and practice test. the data were analyzed through data reduction. Serving the data, and drawing conclussion. The implementation of Joyful learning combining with the humorous strategy proves that this strategy could be trigerred by a humorous poetry or funny video which give a stimulation of fun lerning to students. While, in the teaching leanring process of Sigegh Penguten, there were eight meeting of the implementation and most of the students achieved good as the criterion.Permasalahan dalam penelitian ini adalah bagaimana proses dan hasil pembelajaran tari sigeh penguten menggunakan strategi joyful learning berbantu dengan humor pada kelas VIII di SMP Xaverius Pringsewu. Teori yang digunakan adalah teori behavioristik. Penelitian ini merupakan penelitian deskriptif kualitatif. Sumber data dalam penelitian ini adalah 5 siswa dan guru seni budaya. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi, dan tes praktik. Analisis data penelitian ini adalah reduksi data, penyajian data dan penarikan kesimpulan. Strategi pembelajaran joyful learning berbantu dengan humor adalah strategi yang dapat diciptakan menggunakan pantun jenaka, atau video lucu yang melibatkan guru untuk memberikan rangsangan yang menyenangkan dalam pembelajaran. Pada proses pembelajaran tari sigeh penguten dilaksanakan selama delapan kali pertemuan menunjukan bahwa rata-rata penilaian mendapat kriteria baik.Kata kunci: Joyful Learning, Pembelajaran, Sigeh Penguten.